(untitled) (Clinics, 2012)
OBJECTIVES: This study sought to determine the level of agreement between behavioral and multidimensional pain assessment scales in term newborn infants submitted to an acute nociceptive stimulus. METHODS: This cross-sectional study was performed on 400 healthy term newborns who received an intramuscular injection of vitamin K during the first 6 hours of life. Two behavioral pain scales (the Neonatal Facial Coding System and the Behavioral Indicators of Infant Pain) and one multidimensional tool (the Premature Infant Pain Profile) were applied by a single observer before the procedure, during cleansing, during injection and two minutes after injection. The Cochran Q, McNemar and kappa tests were used to compare the presence and degree of agreement between the three scales. The Hotelling T2 test was used to compare the groups of newborns for which the scales showed agreement or disagreement. A generalized linear regression was used to compare the results of the Neonatal Facial Coding System and the Behavioral Indicators of Infant Pain across the four study time points. RESULTS: The neonates studied had a gestational age of 39±1 weeks, a birth weight of 3169±316 g and and postnatal age of 67±45 minutes. During the stimulus procedure, 80% of the newborns exhibited pain behaviors according to the Neonatal Facial Coding System and the Behavioral Indicators of Infant Pain, and 70% experienced pain according to the Premature Infant Pain Profile (p